2018
DOI: 10.3390/app8030368
|View full text |Cite
|
Sign up to set email alerts
|

Quillaja saponaria Saponins with Potential to Enhance the Effectiveness of Disinfection Processes in the Beverage Industry

Abstract: Featured Application: The extract of Q. saponaria can be used as a pretreatment agent to increase the sensibility of microorganisms to disinfectants. The results can be used to develop a strategy for the control of biofilms in beverage industry.Abstract: This study examines the in vitro effect of Quillaja saponaria extracts on Asaia spp. planktonic cells and biofilms, in comparison and combination with two disinfectants: peracetic acid and N-ethyl-N,N-dimethylhexadecylammonium bromide. The growth of six bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A great number of studies on antibiofilm strategies are focused on surface modification, and many approaches are based on active organosilanes [ 22 , 23 , 24 ] or nanostructured antibacterial multilayers [ 25 , 26 ]. Also, hygienic processes with the application of novel surfactants, stimulating biofilm eradication, have been used [ 27 , 28 ]. However, taking into account the dynamic development of the healthy food trend and the impact on the health and well-being of consumers, a modification of soft drink contents seems much more justified.…”
Section: Resultsmentioning
confidence: 99%
“…A great number of studies on antibiofilm strategies are focused on surface modification, and many approaches are based on active organosilanes [ 22 , 23 , 24 ] or nanostructured antibacterial multilayers [ 25 , 26 ]. Also, hygienic processes with the application of novel surfactants, stimulating biofilm eradication, have been used [ 27 , 28 ]. However, taking into account the dynamic development of the healthy food trend and the impact on the health and well-being of consumers, a modification of soft drink contents seems much more justified.…”
Section: Resultsmentioning
confidence: 99%
“…With these findings, the authors suggest that treatment with saponin solution prior to disinfection may reduce the need for high concentrations of the antimicrobials tested. Concerning the inhibition of bacterial biofilms, experiments conducted in this same study revealed that the extract reduced the live cells number in biofilms by approximately 4 to 5 log [48]. Different studies on the antibacterial activity of Q. saponaria saponins suggest that saponins’ biological activity is related to their chemical constitution, thus different microorganisms have different susceptibilities to saponin action [49,50].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…biopesticide against parasitic nematodes (San Martin et al, 2005), aphids (De Geyter et al, 2012), and as a growth inhibitor of Aedes aegypti and Culex pipiens larvae (Pelah et al, 2002). One of the explanations of this inhibitory effect is the lytic activity of saponins on cell membranes (Sparg et al, 2004;de Geyter et al, 2012) as well as their capacity to change the membrane fluidity and allow macromolecules to get absorbed to or through the cells of an organism (Podolak et al, 2010;Antolak et al, 2018). In other cases, this effect was useful to prevent the attachment or viral infection through cell membranes (Roner et al, 2007;Tam and Roner, 2011) or produce membrane disorders in several organisms at high doses (Sen et al, 1998;Pelah et al, 2002).…”
Section: Use As Vaccine Adjuvantsmentioning
confidence: 99%
“…Antolak et al (2018) FungiAntifungal activity of QS saponins used as a component of cellulose nanofibrous membrane against Penicillium roguefortii and Aspergillus ochraceus Dixit et al (2010). Activity of QS saponins and phenolic compounds against Botrytis cinerea in fresh strawberries coating Zúñiga et al (2012).…”
mentioning
confidence: 99%